Antimicrobial pharmacodynamics of vancomycin and disulfiram (Antabuse®) in Staphylococcus aureus - Chavva, Hasitha; Meka, Yogesh; Long, Timothy E. (Frontiers in Microbiology, 2023)
Intravenous vancomycin is the primary treatment for systemic infections due to methicillin-resistant Staphylococcus aureus. Pharmacokinetic / pharmacodynamic target indices for vancomycin therapies are more difficult to achieve for isolates with an intermediate level of vancomycin resistance. This research investigated the in vitro antimicrobial pharmacodynamic interaction of disulfiram and vancomycin as a potential intervention. Overall, this study established that the addition of disulfiram lowered the minimum inhibitory and bactericidal concentrations of vancomycin in either a synergistic or additive manner. Optimal bactericidal effects and suppression of growth in the vancomycin intermediate resistant strain Mu50 were realized with a 4/8 µg mL-1 combination of vancomycin/disulfiram, but not the individual drugs. Flow cytometry confirmed the enhanced killing action on a cellular level while revealing that disulfiram may counteract the muropeptide fortification mechanism in vancomycin intermediate resistant isolates to sensitize cells to the killing effects of vancomycin.